PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAIPERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Adiatna Permana Putra (2021)
This research aims to determine the influence of financial performance, capital strucuture and firm size on firm value listed on Jakarta Islamic Index in the period 2018 - 2020. The type of this research is quantitative research that uses secondary data based on annual report. A sample of this research consisted of 29 Jakarta Islamic Index companies. Techniques analyzing data in this research used regression model selection test, classical assumption test, multiple linear regression, and partial hypothesis testing (t test). Based on the result of these test, it can be concluded that (1) financial performance has significant influence on firm value, (2) capital structure has no significant influence on firm value, (3) firm size has a significant influence on firm value, and control variable (4) firm age has no significant influence on firm value.